Crystalline loading of lipophilic Coenzyme Q10 pharmaceuticals within conjugated carbon aerogel derivatives. (30th August 2020) - Lim, Matthew B.; Ganas, Abbie S.; Hanson, Jennifer L.; Zhou, Xuezhe; Hellner, Brittney; Manandhar, Sandeep; Gariepy, Rachel E.; Baneyx, François; Wilbur, D. Scott; Pauzauskie, Peter J.
Abstract: Low-density aerogel materials are a promising platform for delivering lipophilic drugs with poor water solubility, but to date, the loading of aerogels with pharmaceuticals in crystalline form has not been reported other than by expensive supercritical loading techniques. Here, we demonstrate a simple and low-cost liquid-phase impregnation method to load the model drug coenzyme Q10 (CoQ10 ) within carbon aerogels. By controlling the chemical microstructure of the aerogel to exhibit π-conjugated (sp 2 ) bonding via addition of graphene oxide, the rate of adsorption and total loading of CoQ10 is significantly enhanced. Furthermore, the adsorbed CoQ10 adopts an as-yet unreported crystalline phase that differs from the bulk material, not only offering the potential advantages of crystalline materials for drug delivery, but also a means to control the microstructure of this important lipophilic pharmaceutical. Graphical abstract: Image 1